2011
DOI: 10.1111/j.1750-3841.2011.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity Changes of 3 Cultivar Chinese Pomegranate (Punica granatum L.) Juices and Corresponding Wines

Abstract: This study investigated the antioxidant capacities that included Ferric reducing antioxidant power (FRAP), 1, 1-diphenyl-2-picryl hydrazine (DPPH), ·OH and O(2·)(-)-scavenging abilities, total polyphenols (TP) and total anthocyanins (TA) in pomegranate (Punica granatum L.) juice (PJ) and pomegranate wine (PW). The correlations among them were also analyzed. Both PJ and PW showed significantly high TP and antioxidant capacities, but some differences existed among these cultivars. There was 1596.67 mg/L TP found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
3
33
1
2
Order By: Relevance
“…On the other hand, Zhuang et al (2011) on green and red peel pomegranate cultivars grown in China found that the juice of the red color cultivar had the highest TA (mg/L) while the sweet green color cultivar had the highest TP (mg/L), however, the sour green color cultivar gave the least values of both attributes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zhuang et al (2011) on green and red peel pomegranate cultivars grown in China found that the juice of the red color cultivar had the highest TA (mg/L) while the sweet green color cultivar had the highest TP (mg/L), however, the sour green color cultivar gave the least values of both attributes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the thermal treatment affected semi-permeability of cellular membrane, resulting in loss of phenolics from the vegetable tissues into the cooking medium. Mass balance analysis showed that boiling caused more dry solid loss as compared to steaming (45).…”
Section: The Effect Of Cooking Methods On Antioxidant Activity Of Vegmentioning
confidence: 99%
“…Phenolic compounds, phenolic acids and flavonoids present in plant materials are known to be strong antioxidants and a positive correlation between the two has been reported in several recent studies (30,(45)(46). In this study, a correlation between total phenolic content and antioxidant activity was determined for all raw and cooked vegetable samples.…”
Section: Correlation Between Total Phenolic Content and Antioxidant Amentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cultivars can also affect wine composition and not all may be useful for optimal fermentation purposes (Towantakavanit, Park, & Gorinstein, 2011). Thus, taking into account the great diversity existing among the sensorial and phytochemical properties of pomegranate cultivars (Mena, García-Viguera et al, 2011), differences in the final quality of pomegranate varietal wines should be expected.Despite these considerations and the fact that some work on pomegranate fermented juices has already been performed (Yae et al, 2007;Zhuang et al, 2011), there is no substantial information on pomegranate wine composition, covering all stages of the pomegranate winemaking process. Cocoa (Theobroma cacao L.) is world-wide known for its beans used in the manufacture of chocolate.…”
mentioning
confidence: 99%